Factor Analysis of Postpartum Blues on Post Partum Patients at Puskesmas Proppo Pamekasan - Hilmah Noviandry Rahman; Byba Melda Suhita (Journal for Quality in Public Health, 2018)
Post Partum Blues (PPB) is sadness or moodiness after delivery which occurs on the third day to two weeks. The incidence of PPB in Indonesia is experienced up to 50-80% of new mothers. Some factors that are suspected to be the cause of PPB are knowledge, type of delivery, husband support, and parity. The purpose of this study was to analyze the factors affecting post partum blues on post partum mothers at Puskesmas Proppo Kabupaten Pamekasan. This research type is quantitative research with cross sectional research design. The study was conducted on January 25 to February 25, 2018 at Puskesmas Pamekasan with 110 postpartum mothers. The sample size is 86 respondents taken with simple random sampling. The independent variables are knowledge, type of labor, support of husband and parity. Dependent variable is post partum blues event. Data were analyzed using logistic regression test with p = 0,05. The results showed that variable X1 (knowledge) with p = 0,007; OR = 8,149, Variable X2 (type of labor) with p = 0,485; OR =1,822, Variable X3 (husband support) with p = 0,005; OR = 4,518, Variable X4 (parity) with p = 0,749; OR = 1,153. So it can be concluded that the factors that affect Y (post partum blues events) is the factor of knowledge and support of the husband, with the most dominant factor is the support of husbands with the effect of 4.581. The low knowledge of postpartum mothers on PPB, and sufficient support of husbands led to the incidence of PPB in Puskesmas Proppo Kabupaten Pamekasan. So it needs health promotion efforts even more intense so as not to happen on PPB.